SAT0611 Canakinumab use in adult familial mediterranean fever patients: a large single centre experience. (12th June 2018) - Babaoglu, H.; Varan, O.; Kucuk, H.; Atas, N.; Satis, H.; Salman, R.B.; Ozturk, M.A.; Goker, B.; Tufan, A.; Haznedaroglu, S.
Abstract : Background: IL-1 blocking agents have been shown to be effective in the prevention of attacks in colchicine resistant FMF (crFMF) patients. Canakinumab is FDA approved long acting recombinant IL-1 receptor antagonist for use in crFMF patients which is available for off label use in Turkey. Herein, we aimed to share our real life single centre experience for use of canakinumab in adult crFMF patients. Methods: Data was derived from Gazi FMF cohort which was established in year 2010. From that date patients with FMF who were diagnosed according to the Tel Hashomer criteria were registered. Co-morbidities, detailed attack characteristics, type, duration, severity, treatments, laboratory parameters and impact of FMF on their life in terms of quality of life and work productivity were recorded either by FMF diary or a mobile phone application (FMF AIDD free to download from AppStore and android market). A retrospective cohort analysis was made from records of patients who were treated with canakinumab. Results: Eighteen adult crFMF patients (%61 female) treated with canakinumab were enrolled in this study. The median age was 31 24–58 years and the median disease duration was 28 16–40 years. All patients harbour homozygous or compound heretozygos exon 10 MEFV mutations. Treatment reasons for canakinumab were colchicine resistance (n=14) and amyloidosis (n=4). In three patients canakinumab was initiated directly, while in 15 it was switched from anakinra (seven was allergic to anakinra, one patient had significant leukopenia, in six fail to control attacks). The median duration of canakinumab use was 8 (min 1- max 22) months. In two patients canakinumab was used as 300 mg/monthly, and in remaining as 150 mg/monthly. Pre- and post-canakinumab periods of patients were compared (Table). Patient reported attack severity (p≤0.01), duration (p≤0.01), frequency (p≤0.01), C-reactive protein (CRP) (p≤0.01) and erythrocyte sedimentation rates (p≤0.01) were significantly improved while serum creatinine and alanine aminotransferase (ALT) levels remained same (p=0.2, p=0.35, respectively). Canakinumab achieved complete disease remission in 5 patients. Side effects requiring discontinuation of canakinumab were observed in none of patients. Conclusions: Canakinumab is effective in the prevention of attacks with a favourable safety profile. Disclosure of Interest: None declared